Hubungan Antara Dukungan Sosial Keluarga Dan Pola Asuh Demokratis Orang Tua Dengan Kematangan Emosi Pada Siswa Kelas XI SMA Negeri 12 Tangerang Selatan - Saragih, Chantika Putri Ramadhani; Herdajani, Febi (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
This study is a quantitative study that aims to determine the relationship between family socialsupport and parents' democratic parenting with the emotional maturity of SMA Negeri 12 SouthTangerang. The sampling technique in this study is probability sampling with research subjects asmany as 160 respondents. The data collection method uses scales, namely emotional maturityscales, family social support, and democratic parenting using Bivariate Correlation analysistechniques with the SPSS 27.0 for windows program. Analysis of family socialsupport with emotional maturity had results with a value of R = 415 p = 0.000 and a relationshipbetween democratic parenting of R = 0.311 p = 0.000. This means that there is a significant positiverelationship between family social support and emotional maturity and there is also a significantpositive relationship between democratic parenting and emotional maturity . Furthermore, theresults of data analysis tests with Multivariate Correlation to measure the relationshipbetween family social support and democratic parenting obtained values R = 0.423, R square 0.179and p = 0.000 (p < 0.05). This shows that there is a relationship between family social support anddemocratic parenting with emotional maturity in Class XI students of SMA Negeri 12 SouthTangerang.